Natural Diversity of Crispr Spacers of Thermus: Evidence of Local Spacer Acquisition and Global Spacer Exchange - Ispolatov, y (Royal Society Publishing, 2019)
We investigated the diversity of CRISPR spacers of Thermus communities from two locations in Italy, two in Chile and one location in Russia. Among the five sampling sites, a total of more than 7200 unique spacers belonging to different CRISPR-Cas systems types and subtypes were identified. Most of these spacers are not found in CRISPR arrays of sequenced Thermus strains. Comparison of spacer sets revealed that samples within the same area (separated by few to hundreds of metres) have similar spacer sets, which appear to be largely stable at least over the course of several years. While at further distances (hundreds of kilometres and more) the similarity of spacer sets is decreased, there are still multiple common spacers in Thermus communities from different continents. The common spacers can be reconstructed in identical or similar CRISPR arrays, excluding their independent appearance and suggesting an extensive migration of thermophilic bacteria over long distances. Several new Thermus phages were isolated in the sampling sites. Mapping of spacers to bacteriophage sequences revealed examples of local acquisition of spacers from some phages and distinct patterns of targeting of phage genomes by different CRISPR-Cas systems. This article is part of a discussion meeting issue The ecology and evolution of prokaryotic CRISPR-Cas adaptive immune systems . © 2019 The Authors. Published by the Royal Society under the terms of the Creative Commons Attribution License http://creativecommons.org/licenses/by/4.0/, which permits unrestricted use, provided the original author and source are credited.